Combinatorial delivery of Ribociclib and green tea extract mediated nanostructured lipid carrier for oral delivery for the treatment of breast cancer synchronising in silico, in vitro, and in vivo studies. (21st November 2022) - Sartaj, Ali, Annu; Alam, Meraj; Biswas, Largee; Yar, Mohammad Shahar; Mir, Showkat Rasool; Verma, Anita Kamra; Baboota, Sanjula; Ali, Javed
Abstract: Purpose: The current research investigated the development and evaluation of dual drug-loaded nanostructure lipidic carriers (NLCs) of green tea extract and Ribociclib. Method: In silico study were performed to determine the effectiveness of combinational approach. The prepared NLCs were subjected to in vitro drug release, lipolysis, haemolysis and cell line studies to assess their in vivo prospect. Results: In silico study was done to get docking score of EGCG (−8.98) close to Ribociclib (−10.78) in CDK-4 receptors. The prepared NLCs exhibited particle size (175.80 ± 3.51 nm); PDI (0.571 ± 0.012); and %EE [RBO (80.91 ± 1.66%) and GTE 75.98 ± 2.35%)] respectively. MCF-7 cell lines were used to evaluate the MTT assay, cellular uptake and antioxidant (ROS and SOD) of prepared NLCs. In vitro drug release showed the controlled release up to 72 h. In vitro lipolysis and in vitro haemolysis studies showed the availability of drugs at absorption sites and the greater in vivo prospects of NLCs respectively. Pharmacokinetic study revealed a 3.63-fold and 1.53-fold increment in RBO and GTE bioavailability in female Wistar rats respectively. Conclusion: The prominent potential of green tea extract and RBO-loaded NLCs in enhancing their therapeutic efficacy for better treatment of breast cancer.